Sepsis of digestive origin. - Correa Rivero, Humberto; Patrone, Luis (Cirugía del Uruguay, 1983)
2.4% of ali patients recibed in an lntensive (Polivalent) Care Unit. A colonic origin was found in the 30 % of cases. 67 % were spontaneous, while the other 33 % follows gastrointestinal surgery. The mortality rate was 75 %.